Návrh a tvorba edukační aplikace pro děti základních škol - Bernáth, Radoslav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Táto bakalárska práca sa zameriava na návrh multiplatformovej mobilnej aplikácie pre Základnú školu. Aplikácia je určená pre žiakov a učiteľov Základnej školy Benkova v Nitre. Učitelia budú môcť jednoducho vytvárať testy pre svojich žiakov s možnosťou interaktívnej formy v podobe hry.

This bachelor thesis focuses on the design of a multiplatform mobile application for primary school. The application is intended for students and teachers of the Benkova Primary School in Nitra. Teachers will be able to easily create tests for their students with the possibility of an interactive form in the form of a game.
Design and Creation of an Educational Application for Primary School Children
Keywords: Andriod; iOS; herný engine; hra; test; diagram prípadov použitia; ER diagram; vývojový diagram; analýza SWOT; Andriod; iOS; game engine; game; test; use case diagram; ER diagram; flowchart; SWOT analysis